How event quality affects satisfaction and revisit intention from the theory of planned behaviour - Jaffry bin Zakaria, Omar Firdaus bin Mohd Said (Tanjung Malim, 2024)
How event quality affects satisfaction and revisit intention from the theory of planned behaviour by Jaffry bin Zakaria, Omar Firdaus bin Mohd Said